Methodological aspects in gastroenteric methane evaluation trial in water buffalo - Maria Chiara La Mantia; Emanuela Rossi; Francesco Cenci; David Meo Zilio; Roberto Steri; Miriam Iacurto; Antonella Chiariotti (Revista Científica)
Methane (CH 4) is a potent greenhouse gas, and ruminants constitute a significant source of agricultural contributions. It has been hypothesized that the host’s genome ultimately controls rumen microbial communities, but numerous samples are needed to achieve robust results. The ease and representativeness of the sampling method and the cost-efficiency of large-scale sequencing will, therefore, be major factors in ensuring the feasibility of a research project. The rationale of this work was to verify if non-invasive samples could be a proxy for ruminal digesta and to validate the concentration registered by a laser methane detector (LMD) at the nostrils by measuring the actual concentration of CH4 at the rumen cannula immediately after opening. The LMD is a remote CH4 monitoring system for air used in other ruminants, but studies on buffalo are scarce. The laser beam is pointed toward the source to acquire the data. The trial aimed to compare an easy sampling (1’ during a milking session), with a longer and labor-intensive one (5’ animals captured in a crash). In five (n=5) cannulated buffalo cows, various matrices (whole rumen content, feces, and buccal swabs) were tested for DNA recovery. Two different Buccal swabs were tested. Frozen solid and liquid rumen fractions, feces as-is, pelleted, or in preserving glycerol solution at room temperature were tested. Different protocols for DNA extraction (WUR protocol; Kit Maxwell® Promega; Kit Quick Extract™ Lucigen) and various sampling methods were compared. Saliva was a difficult matrix to process and did not yield satisfactory DNA, so it is unsuitable as a proxy. Feces showed no difference in preservation methods, and DNA recovery was like the rumen. Nevertheless, metagenomic analysis must be carried out to verify whether the species composition is comparable. All DNA extraction methods were satisfying: Quick Extract was the easiest to perform, WUR resulted in the highest amount of DNA, and Kit Maxwell was the one that gave the overall best performance. As for the CH4 measure, there was a significant correlation between the rumen’s highest pick value of emission at the cannula and the intensity and duration of breath emission, calculated as breath + eructation. Moreover, we found a highly significant difference in emissions patterns when animals were subjected to distress (confinement, manipulation). LMD showed different emission trends under different sampling conditions, which seems suitable for CH4 measurement in the buffalo species.